2013
DOI: 10.1177/0886260513487995
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Attitudes Toward Rape are Associated With Sexual Aggression

Abstract: We examined the relationship between self-reported sexual aggression and implicit and explicit attitudes towards rape in a sample of 86 male heterosexual university students. Large, significant group differences were found between the most sexually aggressive participants and the nonaggressive participants, with the most sexually aggressive group showing less negative implicit and explicit attitudes towards rape (Cohen's d=0.76-1.20). Implicit and explicit attitudes provided complementary information such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(139 citation statements)
references
References 52 publications
7
123
1
3
Order By: Relevance
“…Do the semantic differential scales we used in the current study actually reflect attitudes and identification? Nevertheless, our semantic differential scales are undoubtedly an incomplete assessment of the constructs of interest and future research should examine other self-report measures as well as implicit measures (Bluemke & Zumbach, 2012;Eckhardt et al, 2012;Nunes, Hermann, & Ratcliffe, 2013;Polaschek et al, 2010;Robertson & Murachver, 2007;Snowden et al, 2004). Although the specific semantic differential scales we used in the current study have not been validated per se, the use of similar semantic differential scales is a widespread, long-standing, and validated approach to assessing key constructs in social-psychological research (e.g., Gawronski & Bodenhausen, 2006;Glasman & Albarracín, 2006;Hofmann et al, 2005;Osgood et al, 1957;Taylor, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Do the semantic differential scales we used in the current study actually reflect attitudes and identification? Nevertheless, our semantic differential scales are undoubtedly an incomplete assessment of the constructs of interest and future research should examine other self-report measures as well as implicit measures (Bluemke & Zumbach, 2012;Eckhardt et al, 2012;Nunes, Hermann, & Ratcliffe, 2013;Polaschek et al, 2010;Robertson & Murachver, 2007;Snowden et al, 2004). Although the specific semantic differential scales we used in the current study have not been validated per se, the use of similar semantic differential scales is a widespread, long-standing, and validated approach to assessing key constructs in social-psychological research (e.g., Gawronski & Bodenhausen, 2006;Glasman & Albarracín, 2006;Hofmann et al, 2005;Osgood et al, 1957;Taylor, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Further, although several studies have demonstrated the validity of the IAT (e.g. Eckhardt et al, 2012;Nunes, Hermann, & Ratcliffe, 2013), more studies are required to confirm its clinical and diagnostic usefulness.…”
Section: Discussionmentioning
confidence: 96%
“…ROE Scale scores can range from -63 (indicating an extremely negative attitude towards rape) to +63 (indicating an extremely positive attitude towards rape). We have found that higher scores on both the evaluation and overall ROE Scale are associated with higher selfreported likelihood to rape (Nunes et al, 2011). RAPE Scale.…”
Section: Methodsmentioning
confidence: 98%